The need for an integrated theoretical framework for researching the influence of group diversity on performance - Qin, J.; O'Meara, B.; McEachern, Steven (Barmarick Publications, 2009)
Purpose – Investigating diversity presents researchers with a paradox because extremely inconsistent and conflicting findings about the effects of diversity have emerged in this field of study. It has been argued that the theoretical frameworks used have contributed to the paradox. Different and contradictory effects concerning the influence of group diversity can be predicted using these frameworks. The purpose of this paper is to examine the application of the main theoretical frameworks in the context of researching diversity.Design/methodology/approach – The focus of this paper is a critical examination of three theoretical frameworks in the field of diversity research – similarity-attraction theory, social categorization theory and the information/decision-making approach. These are commonly applied in researching diversity. The basic elements of each theory, its applications in diversity research and its strengths and limitations are considered.Findings – The discussion suggests that the paradox in diversity research emerges from a research tradition that views the three frameworks as being best applied separately because each framework predicts different and even contradictory outcomes. These differences are a consequence of distinctive theoretical operations. In addition, the strengths and limitations associated with each theoretical framework suggest that they might be integrated and subsequently applied in specific settings according to their respective strengths and limitations.Research limitations/implications – In order to produce more consistent results in research on diversity, it is suggested that future researchers should not rely solely on a single theoretical framework to predict the effects of diversity. In particular, different theoretical frameworks may work well with certain types of diversity as well as certain levels of analysis.Originality/value – The paper provides a framework for dissecting the diversity paradox and a foundation for designing fresh approaches that might produce findings that are more consistent.Keywords:Groups, Social stratification, Social structure, The information/decision-making approachArticle Type:Research paperArticle URL:http://www.emeraldinsight.com/10.1108/01409170910977951